All-cause mortality in adults with and without type 2 diabetes: findings from the national health monitoring in Germany. Issue 1 (16th December 2017) - Röckl, Susanne; Brinks, Ralph; Baumert, Jens; Paprott, Rebecca; Du, Yong; Heidemann, Christin; Scheidt-Nave, Christa
Abstract : Objective: To estimate age-specific and sex-specific all-cause mortality among adults with and without type 2 diabetes (T2D) in Germany. Research design and methods: The German National Health Interview and Examination Survey 1998 (GNHIES98) included a mortality follow-up (median follow-up time 12.0 years) of its nationwide sample representative of the population aged 18–79 years. After exclusion of participants with type 1 diabetes, age- and sex-stratified mortality rates (MR) were calculated for 330 GNHIES98 participants with diagnosed T2D (self-reported diagnosis or antidiabetic medication), 245 with undiagnosed T2D (no diagnosed T2D, glycated hemoglobin A1c ≥6.5% (≥48 mmol/mol)), and 5975 without T2D. Mortality rate ratios (MRR) comparing MR of persons with and without T2D were estimated. Age-/sex-standardized MR and MRR were calculated including persons aged 45 years or older. MRR were used to estimate the number of years of life lost (YLL) due to diagnosed diabetes in 2010. Results: Over 75 994 person-years, 73 persons with undiagnosed T2D, 103 with diagnosed T2D, and 425 persons without T2D died. MRR were significantly higher in younger age groups, except for analyses limited to women or diagnosed T2D. Age- and sex-standardized MRR (95% CI) among persons aged 45 years or older were 1.96 (1.41 to 2.71) for undiagnosed, 1.68 (1.26 to 2.23) for diagnosed, and 1.82 (1.45 to 2.28) for total (undiagnosed or diagnosed) T2D. Sex-stratified analysis revealed similar age-standardized MRR for undiagnosed (1.56 (0.79 to 3.06)) and diagnosed T2D (1.56 (1.03 to 2.37)) among women, and a higher age-standardized MRR for undiagnosed (2.06 (1.43 to 2.97)) than diagnosed T2D (1.70 (1.10 to 2.63)) among men. YLL due to diagnosed diabetes in Germany in 2010 were 164 600 (35 000 to 279 300) among women and 169 900 (28 300 to 328 300) among men. Conclusions: In Germany, age- and sex-standardized all-cause mortality is almost twice as high for adults with T2D as for adults without T2D. The T2D-associated excess risk of mortality appears to be most pronounced in younger adults and among men unaware of their T2D.